Cost-effectiveness of different strategies to prevent breast and ovarian cancer in German women with a BRCA 1 or 2 mutation - Müller, Karsten; Danner, Marion; Rhiem, Kerstin; Stollenwerk, Björn; Engel, Christoph; Rasche, Linda; Borsi, Lisa; Schmutzler, Rita; Stock, Stephanie (The European journal of health economics : HEPAC : health economics in prevention and care, 2018)
BACKGROUND Women with a BRCA1 or BRCA2 mutation are at increased risk of developing breast and/or ovarian cancer. This economic modeling study evaluated different preventive interventions for 30-year-old women with a confirmed BRCA (1 or 2) mutation. METHODS A Markov model was developed to estimate the costs and benefits [i.e., quality-adjusted life years (QALYs), and life years gained (LYG)] associated with prophylactic bilateral mastectomy (BM), prophylactic bilateral salpingo-oophorectomy (BSO), BM plus BSO, BM plus BSO at age 40, and intensified surveillance. Relevant input data was obtained from a large German database including 5902 women with BRCA 1 or 2, and from the literature. The analysis was performed from the German Statutory Health Insurance (SHI) perspective. In order to assess the robustness of the results, deterministic and probabilistic sensitivity analyses were performed. RESULTS With costs of \text€29,434 and a gain in QALYs of 17.7 (LYG 19.9), BM plus BSO at age 30 was less expensive and more effective than the other strategies, followed by BM plus BSO at age 40. Women who were offered the surveillance strategy had the highest costs at the lowest gain in QALYs/LYS. In the probabilistic sensitivity analysis, the probability of cost-saving was 57% for BM plus BSO. At a WTP of 10,000 \text€ per QALY, the probability of the intervention being cost-effective was 80%. CONCLUSIONS From the SHI perspective, undergoing BM plus immediate BSO should be recommended to BRCA 1 or 2 mutation carriers due to its favorable comparative cost-effectiveness.